Early Sri Lankan coastal site tracks technological change and estuarine resource exploitation over the last ca. 25,000 years - Noel Amano; Patrick Faulkner; Oshan Wedage; Chris Clarkson; Dambara Amila; Miren del Val; Dovydas Jurkenas; Alexander Kapukotuwa; Gloria I. López; Josep Pares; M. M. Pathmalal; Tam Smith; et al. (Scientific Reports)
Abstract The island of Sri Lanka was part of the South Asian mainland for the majority of the past 115,000 years, and connected most recently during the Last Glacial Maximum via the now submerged Palk Strait. The degree to which rising sea levels shaped past human adaptations from the Pleistocene and into the mid to late Holocene in Sri Lanka has remained unclear, in part because the earliest reliable records of human occupation come from the island’s interior, where cave sites have revealed occupation of tropical forest ecosystems extending back to 48 thousand years (ka). The island’s earliest known open-air sites are all much younger in date, with ages beginning at 15 ka and extending across the Holocene. Here we report the earliest well-dated open-air coastal site in Sri Lanka, Pathirajawela, which records human occupation back to ca. 25,000 years ago. We show that humans at Pathirajawela consistently adapted to changing ecosystems linked to sea level transgression and coastal evolution from the Last Glacial Maximum into the Holocene. The presence of anthropogenic shell midden deposits at the site from ca. 4.8 ka, focused almost exclusively on a single taxon, indicates intensification of estuarine resource exploitation, as humans responded to opportunities presented by the formation of new coastal ecosystems.